PEMAKNAAN NILAI NILAI SPIRITUAL WELL BEING DALAM KEHIDUPAN KELUARGA MUSLIM - Nisa Rachmah Nur Anganthi; Zahrotul Uyun (Universitas Muhammadiyah Semarang, 2015)
This article propose the meaning of spiritual values on Moslem family from Husband’s perspective. Islamic perspective consider “husband” as a “leader” in his family that lead for family members to gain of well-being condition. The research aims to identify spiritual values of family well-being based on social-spiritual philosophy background. Respondents consist of 4 lecturers and 5 staffs who work on Islamic Higher Eduction in Surakarta. The research uses qualitative approach by purposive sampling. Respondents have characteristic are a man, minimum age 30 years old, he works 3 years, and education level is diploma. The data gathering from interview and documentation. The finding is sosial-religious philosophy background gives the different perspective about how to understanding, meaning, and implementing spiritual well-being values, especially in the social-life context. The contrary, in the family-life context respondents show are similar in religiousity values orientation. The conclusion that the variety of social-religious philosophy background will indicate variety of understanding and meaning of spiritual well-being values. Athough there are different meaning, but there are similar perspective to implementing spiritual well-being values on the family-life. The implication of research is necessary to reinforce spiritual well-being values, especially on social-community through dialog and communication between families or family members to minimize differentiation or misunderstanding.Keywords: meaning, spiritual well-being, moslem family